IMPLICATIONS OF ECONOMIC LAW AND HEALTH LAW ON SANCTIONS FOR PETTY THEFT OFFENDERS IN INDONESIA - Gunawan Widjaja (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study discusses the implications of economic law and health law on sanctions for petty theft offenders in Indonesia with a literature review approach. The adjustment of the minor theft loss limit through PERMA No. 2 Year 2012 from IDR250 to IDR2.5 million reflects the legal response to economic dynamics, aiming to increase the efficiency of law enforcement and reduce the burden on the state budget through the transfer of sanctions from imprisonment to fines or community service. However, the application of health aspects, particularly the mental and socio-economic conditions of perpetrators, has not been formally integrated in the criminalisation system, so perpetrators from vulnerable groups are still at risk of receiving disproportionate sanctions. This research recommends the revision of regulations and technical guidelines that integrate economic and health considerations in determining sanctions, in order to realise a more efficient, fair and humane criminal justice system.